(untitled) (Asian Journal of Social Science Studies, 2017)
Alternative taxi service has started becoming a trend and gained popularity all over the world. In Malaysia, people depend on conventional taxis for many decades which are registered under Public Transport Commission. With the advancement of technology, a few applications were introduced and passengers and conventional taxi drivers started installing them to accept or reject passengers. However, when the popular American alternative taxi service (Uber) arrived in Malaysia, it has become popular among passengers when new drivers emerged as many people started registering and using the application. The study attempts to explore the language needs of Malaysian taxi drivers (particularly alternative taxi service) and the challenges they face when communicating in the English Language with their passengers. A case study design was employed in the study which a total of three participants (part-time drivers living in Klang Valley area, registered under the same alternative taxi company in Malaysia) were interviewed through open-ended and semi structured interview questions. The findings show there are three main challenges faced by these drivers when communicating in English Language with their passengers which are (1) struggle to comprehend communication in English Language with native speakers, (2) difficulty in making conversations and keeping them going, and (3) difficulty in understanding and communicating with non-native speakers from non-English Language speaking countries. Another findings show that the English Language is used with passengers for four reasons: (1) using English Language to reply passengers’ text message, (2) using English Language to spark general conversation with passengers, (3) using English Language to communicate with foreign passengers; and (4) using English Language to convey precise information to passengers. Therefore, alternative taxi companies should consider offering courses related to enhancing their drivers’ competency in English communication. English courses developed explicitly for the purpose of communication between drivers and passengers may take the results found from this study into account. The findings should be able to assist in developing a course that would aid drivers into strategizing their communication with passengers.